2019
DOI: 10.7717/peerj.7603
|View full text |Cite
|
Sign up to set email alerts
|

Mapping research trends of retinal vein occlusion from 2009 to 2018: a bibliometric analysis

Abstract: Objectives To map publication trends and explore research hotspots of retinal vein occlusion (RVO) study. Methods Based on Web of Science Core Collection (WoSCC), a bibliometric analysis was carried out. The knowledge map was constructed by VOSviewer v.1.6.10 to visualize the annual publication number, the distribution of countries, international collaborations, author productivity, source journals, cited reference and keywords in this fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Risk factors of RVO are known to include hypertension, systemic vascular disease, hyperlipidemia, pregnancy, oral contraceptive use, and hypercoagulability; however, the underlying pathogenesis of RVO remains unclear [3]. Interestingly, some studies have shown that local and systemic inflammation can induce both atherosclerosis and systemic hypercoagulability, which influence the development of ME secondary to RVO (RVO-ME) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors of RVO are known to include hypertension, systemic vascular disease, hyperlipidemia, pregnancy, oral contraceptive use, and hypercoagulability; however, the underlying pathogenesis of RVO remains unclear [3]. Interestingly, some studies have shown that local and systemic inflammation can induce both atherosclerosis and systemic hypercoagulability, which influence the development of ME secondary to RVO (RVO-ME) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Study reported that 118 clinical trials and 135 preclinical studies were published in leading journals 19 . Moreover, an interesting study figures out that 2,135 peer-reviewed papers were published from 2009 to 2018 on retinal vein occlusion (RVO) a subspecialty of ophthalmology from Web of Science Core Collection to identify potential collaborators and partner institutions 20 . Lastly, assessing gaps are important to researchers between the specialty and subspecialty of visual sciences to categorize the objectives for achieving goals in future.…”
Section: Resultsmentioning
confidence: 99%
“…The visualized analysis in this study applied GraphPad Prism 8, VOSviewer1.6.16, and Citespace.5.7.R2 as described previously [47]. GraphPad Prism is a drawing tool widely used in scienti c research.…”
Section: Visualized Analysismentioning
confidence: 99%